Mastering System Center 2012 R2 Configuration Manager - Martinez, Santos, 1982-; Daalmans, Peter; Bennett, Brett (Software engineer) (Sybex, 2014)
Invaluable coverage on all aspects of System Center 2012 R2 Configuration Manager Completely updated for System Center 2012 R2 Configuration Manager, this comprehensive book provides intermediate and advanced coverage of all aspects of the product, including planning and installation, migrating from previous versions of Configuration Manager, deploying software and operating systems, security, monitoring and troubleshooting, and automating and customizing. Provides numerous real-world scenarios to show you how to use the tool in various contexts Explores planning and installation and migrating from SCCM 2007 Walks you through deploying software and operating systems, security, monitoring, and troubleshooting Demonstrates automating and customizing SCCM 2012 with scripts This essential book provides you with all the information you need to get savvy with System Center 2012 R2 Configuration Manager.